Nesting cormorants and temporal changes in Island habitat. Issue 2 (February 2014) - Hebert, Craig E.; Pasher, Jon; Weseloh, D.V. Chip; Dobbie, Tammy; Dobbyn, Sandy; Moore, David; Minelga, Valerie; Duffe, Jason
ABSTRACT Double‐crested cormorant (Phalacrocorax auritus) populations have increased greatly across North America. The interior North America subpopulation is the largest with many birds nesting on the Laurentian Great Lakes. Lake Erie supports a large number of breeding pairs that nests primarily on islands in the western basin of the lake. These islands also harbor many rare plant species constituting some of the last vestiges of Carolinian plant communities in Canada. Nesting cormorants can adversely affect the plant communities on the islands on which they nest. Annual ground censuses were conducted from 1979 to 2011 to assess temporal changes in the density of nesting cormorants on 3 islands in western Lake Erie. We used aerial photographs taken over a maximum 16‐year span to assess changes in forest cover on these island ecosystems. We observed declines in forest cover on all 3 islands ranging from 47% to 85%. Trends among islands differed reflecting differences in cormorant colonization histories and the degree to which cormorants were managed, thereby influencing nest densities. Islands without cormorant management had cormorant nest densities ranging from approximately 300–500 nests/ha and forests declined continuously through time. On the island where cormorants were culled, nest densities were lower (approx. 200 nests/ha) and forest decline stabilized. © 2014 The Wildlife Society.